Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/pr401267m
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Phase I/II Personalized Therapy Trial for Metastatic Colorectal Cancer: Evaluating the Feasibility of Protein Pathway Activation Mapping for Stratifying Patients to Therapy with Imatinib and Panitumumab

Abstract: This nonrandomized phase I/II trial assessed the efficacy/tolerability of imatinib plus panitumumab in patients affected by metastatic colorectal cancer (mCRC) after stratification to treatment by selection of activated imatinib drug targets using reverse-phase protein array (RPPA). mCRC patients presenting with a biopsiable liver metastasis were enrolled. Allocation to the experimental and control arms was established using functional pathway activation mapping of c-Kit, PDGFR, and c-Abl phosphorylation by RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…On this latter point, kinase-substrate analysis (KSEA) [34] and integrated personalized signatures (pCHIPS) [35] have recently been proposed for kinase pathway activity or drug prioritization, but these methods have not been validated for single clinical samples. Antibody-based protein arrays may provide a more high-throughput alternative phosphoproteomics approach and have shown potential for the identification of treatment targets [36] and patient stratification [37]. Drawbacks of this approach are the limited number of phosphosite-specific antibodies targeting assumed epitopes of interest [20,38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…On this latter point, kinase-substrate analysis (KSEA) [34] and integrated personalized signatures (pCHIPS) [35] have recently been proposed for kinase pathway activity or drug prioritization, but these methods have not been validated for single clinical samples. Antibody-based protein arrays may provide a more high-throughput alternative phosphoproteomics approach and have shown potential for the identification of treatment targets [36] and patient stratification [37]. Drawbacks of this approach are the limited number of phosphosite-specific antibodies targeting assumed epitopes of interest [20,38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Jameson et al recently reported a turn-around-time of 12–23 days (median 15.5 days) in a multi-site, multi-omic clinical trial (Side-Out, Table 1) in which fresh biopsies were subjected to immunohistochemistry, cDNA microarray analysis, and LCM prior to RPPA [5]. The turnaround-time for LCM-RPPA of clinical biopsy samples in our clinical trials ranges from 3 – 10 business days from biopsy to report [5, 22] [Dr. M. Pierobon, 8 Oct 2014, written personal communication]. Microdissection of heterogeneous tissue samples is required to obtain meaningful information that can reveal unique protein pathway signatures of a patient’s tumor, which in turn can be exploited as therapeutic targets.…”
Section: Integration Of Laser Capture Microdissection In Rppa Basementioning
confidence: 99%
“…Nonetheless, new molecular targets and combination therapies are actively being evaluated in clinical trials, expediting the translation of basic research into clinical applications (Table 1). RPPA analysis includes the following functional information about the state of actionable drug targets: a) protein signal pathway network analysis, b) upstream/downstream linkage analysis, c) protein signaling across classes of samples/treatments, d) predictive treatment efficacy and patient stratification, and e) post-translational proteomic data [5, 20–22]. This data is unattainable by genomic and transcriptomic analyses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations